A Play of Points Of View on Narration of the Novel Thérèse Desqueyroux of François Mauriac - Kundelis, Tadas; Bikulčius, Vytautas (Literatūra, 2017)
A play of points of view on narration of the novel Thérèse Desqueyroux of François Mauriac is being analysed in the paper. Drawing on the theory of narrative of Wolf Schmid and Gérard Genette, we have found that such a play of points of view is related to temporal, ideological and linguistic levels. It is up to an author, in this case François Mauriac, to reveal his point of view or not. On temporal level, we can speak about text interference: a play of points of view on narration starts when the same sentence belongs to the both, the narrator and the protagonist. On the other hand, a sharp transition between the past-the present-the future may be related to two sentences or two elements of one sentence. In this way François Mauriac demonstrates ambivalent temporality of his text. Ideological level of the novel is created by dialogues between the extradiegetic narrator and the protagonists. The narrator holds a discussion with a particular ideology hidden within the text. Meanwhile dialogues between Thérèse and the family are not built on ideology. On linguistic level, the narrator replaces first-person narration with third-person narration seeking to identify the protagonist and time that pertains to temporal level. Sometimes it becomes difficult to identify the main sentence of narrative because discourses of the both, the narrator and the protagonist, become balanced in the text of the novel.